Virulence Characterization of International Collections of the Wheat Stripe Rust Pathogen, Puccinia striiformis f. sp. tritici - Sharma-Poudyal, D (Plant disease, 2013)
Wheat stripe rust (yellow rust [Yr]), caused by Puccinia striiformis f. sp. tritici, is an economically important disease of wheat worldwide. Virulence information on P. striiformis f. sp. tritici populations is important to implement effective disease control with resistant cultivars. In total, 235 P. striiformis f. sp. tritici isolates from Algeria, Australia, Canada, Chile, China, Hungary, Kenya, Nepal, Pakistan, Russia, Spain, Turkey, and Uzbekistan were tested on 20 single Yr-gene lines and the 20 wheat genotypes that are used to differentiate P. striiformis f. sp. tritici races in the United States. The 235 isolates were identified as 129 virulence patterns on the single-gene lines and 169 virulence patterns on the U.S. differentials. Virulences to YrA, Yr2, Yr6, Yr7, Yr8, Yr9, Yr17, Yr25, YrUkn, Yr28, Yr31, YrExp2, Lemhi (Yr21), Paha (YrPa1, YrPa2, YrPa3), Druchamp (Yr3a, YrD, YrDru), Produra (YrPr1, YrPr2), Stephens (Yr3a, YrS, YrSte), Lee (Yr7, Yr22, Yr23), Fielder (Yr6, Yr20), Tyee (YrTye), Tres (YrTr1, YrTr2), Express (YrExp1, YrExp2), Clement (Yr9, YrCle), and Compair (Yr8, Yr19) were detected in all countries. At least 80% of the isolates were virulent on YrA, Yr2, Yr6, Yr7, Yr8, Yr17, YrUkn, Yr31, YrExp2, Yr21, Stephens (Yr3a, YrS, YrSte), Lee (Yr7, Yr22, Yr23), and Fielder (Yr6, Yr20). Virulences to Yr1, Yr9, Yr25, Yr27, Yr28, Heines VII (Yr2, YrHVII), Paha (YrPa1, YrPa2, YrPa3), Druchamp (Yr3a, YrD, YrDru), Produra (YrPr1, YrPr2), Yamhill (Yr2, Yr4a, YrYam), Tyee (YrTye), Tres (YrTr1, YrTr2), Hyak (Yr17, YrTye), Express (YrExp1, YrExp2), Clement (Yr9, YrCle), and Compair (Yr8, Yr19) were moderately frequent (>20 to <80%). Virulence to Yr10, Yr24, Yr32, YrSP, and Moro (Yr10, YrMor) was low (≤20%). Virulence to Moro was absent in Algeria, Australia, Canada, Kenya, Russia, Spain, Turkey, and China, but 5% of the Chinese isolates were virulent to Yr10. None of the isolates from Algeria, Canada, China, Kenya, Russia, and Spain was virulent to Yr24; none of the isolates from Algeria, Australia, Canada, Nepal, Russia, and Spain was virulent to Yr32; none of the isolates from Australia, Canada, Chile, Hungary, Kenya, Kenya, Nepal, Pakistan, Russia, and Spain was virulent to YrSP; and none of the isolates from any country was virulent to Yr5 and Yr15. Although the frequencies of virulence factors were different, most of the P. striiformis f. sp. tritici isolates from these countries shared common virulence factors. The virulences and their frequencies and distributions should be useful in breeding stripe-rust-resistant wheat cultivars and understanding the pathogen migration and evolution